Analyzing Factors Affecting the Success of Social Media Posts for B2b Networks: A Fractional-Factorial Design Approach - Kontsevaia, Diana B; Berger, Paul D (International Journal of Business, Economics and Management, 2017)
This paper explores the determining of which factors/variables, and the optimal levels of these factors that lead toward successful online posts in a B2B context. Using real data from a software development company’s official social media outlets, data made available only to the authors, we conducted a fractional-factorial design with two dependent (output) variables, which were measures of success: number of impressions, and number of actions. We examined the impact of six independent variables (“factors”) and some selected interactions of these factors on the two output measures. The factors are: day of post, time of day of post, presence of an image, presence of a hashtag, length of the message, and specific channel used. Three of the six factors were significant when analyzing number of impressions, while none of the factors made the 5% significance level when analyzing number of actions.